The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1210/en.2011-1681
|View full text |Cite
|
Sign up to set email alerts
|

GH Does Not Modulate the Early Fasting-Induced Release of Free Fatty Acids in Mice

Abstract: Fasting results in the mobilization of adipose stores and the elevation of levels of free fatty acids (FFA). In humans, this process is driven by a release in GH. Little is known regarding the role of GH in modulating this process during early stages of fasting in the mouse. Confirmation of the role of GH in modulating FFA release in the fasting mouse is of particular importance given the frequent use of mouse models to study metabolic mechanisms. Here, we correlate the initial release of FFA throughout fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 49 publications
4
38
0
2
Order By: Relevance
“…Corroborating previous reports, a 24 h fast significantly reduced body weight [34] and altered systemic markers of fed status including plasma glucose, NEFA, insulin, and leptin [21, 22, 35, 36]. This study further demonstrates that a 24 h fast is sufficient to reduce cytokine expression in the blood and WAT under nonstressed conditions.…”
Section: Discussionsupporting
confidence: 88%
“…Corroborating previous reports, a 24 h fast significantly reduced body weight [34] and altered systemic markers of fed status including plasma glucose, NEFA, insulin, and leptin [21, 22, 35, 36]. This study further demonstrates that a 24 h fast is sufficient to reduce cytokine expression in the blood and WAT under nonstressed conditions.…”
Section: Discussionsupporting
confidence: 88%
“…Intrinsic to this method is frequent handling of the mice during bleeding, which is likely to activate the stress response. Although the handling stress was claimed to be negligible, reported corticosterone levels were relatively high at 370 ng/mL (51). Thus, our automated method has the advantage of obtaining serial blood samples from individual mice for extended periods of time during the day or night for the analysis of hormone patterns in the absence of activating the stress axis.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is likely that species-specific differences exist regarding the metabolic effects of GH; for instance, one study observed that GH does not modulate the initial release of FFA during fasting in the mouse [82]. Likewise, the epididymal fat pad, which has been most commonly used for mouse studies, has no clinical equivalent, requiring one to use caution in interpreting the clinical relevance of these studies.…”
Section: Discussionmentioning
confidence: 99%